Development Of Multiwalled Carbon Nanotubes Reinforced Hydroxyapatite - Gholami, Fatemeh (2014)
The similarity of the chemical composition of hydroxyapatite (HA) to the mineral phase of bone and their excellent biocompatibility meets the requirement of materials designed for bone repair and augmentation purposes. However, the application of HA in load bearing devices is limited by its poor mechanical properties. Persamaan komposisi kimia hidroksiapatit (HA) dengan fasa mineral tulang dan keserasian biologinya yang sangat baik memenuhi keperluan bahan reka bentuk untuk pembesaran dan pembaikan tulang. Walaubagaimanapun, aplikasi HA dalam peranti menanggung beban adalah terhad disebabkan ciri mekanikal yang lemah.